3D Aural Interactive Hyperstories for Blind Children - Lumbreras, Mauricio; Sánchez, Jaime (International Journal of Virtual Reality, 1999)
Interactive stories are commonly used for learning and entertainment purposes and enhance the development of several perceptual and cognitive skills. These experiences are not very common among blind children because most computer games and electronic toys do not have accessible sound interfaces. This study introduces the idea of interactive hyperstories performed in a 3D acoustic virtual world. The hyperstory model enables us to build an application to help blind children to enrich their early world experiences through exploration of interactive virtual worlds by using 3D aural representations of the space. We have produced AudioDoom, an interactive model-based software for blind children. The prototype was qualitatively and quantitatively field-tested with several blind children in a Chilean school setting. Our preliminary results indicate that when acousticbased entertainment applications are carefully applied with an appropriate methodology they can be used without visual cues. We also found that spatial sound experiences can create spatial navigable structures in the minds of blind children. Methodology and usability evaluation procedures and results appeared to be critical to the efectiveness of interactive Hyperstories performed in a 3D acoustic virtual world.